Liquidity constraints and linkages with multinationals - Mariana Spatareanu; Beata S. Javorcik (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2008)
Using a unique data set from the Czech Republic for 1994-2003, this study examines the relationship between a firm's liquidity constraints and its supply linkages with multinational corporations (MNCs). The empirical analysis indicates that Czech firms supplying MNCs are less credit constrained than non-suppliers. A closer inspection of the timing of the effect, however, suggests that this result is due to less constrained firms self-selecting into becoming MNC suppliers rather than the benefits derived from the supplying relationship. As recent literature finds that productivity spillovers from foreign direct investment (FDI) are most likely to take place through contacts between MNCs and their local suppliers, our finding suggests that well-developed financial markets may be needed in order to take full advantage of the benefits associated with FDI inflows.
Keywords: 330; foreign direct investment; cash flow; liquidity constraints